Do Funded Pensions Contribute to Higher Aggregate Savings? A Cross-Country Analysis - Bailliu, Jeanine (OECD Development Centre Working Papers, 1997)
This paper provides statistically significant international evidence on the interaction between funded pensions and aggregate savings, after controlling for country-specific effects and for other saving determinants that have typically been identified in earlier cross-country studies. Using panel data for eleven countries (both OECD and non-OECD), this study goes beyond earlier work which has been based on individual country studies only (which have suffered from a small number of degrees of freedom). Building several proxies of pension wealth based on internationally comparable pension fund and life insurance data, the paper estimates the relationship between aggregate saving rates and pension wealth using ordinary least squares and two-stage least squares over the 1982-93 period. The empirical analysis supports the predictions of a simple two-period life-cycle saving model that incorporates tax treatment of pension returns, population heterogeneity, capital market imperfection and ...